MODELING THE RELATIVE MOTION OF MAGNETIC LEVITATING TRAIN - Poliakov, V. O.; Khachapuridze, M. M. (Science and Transport Progress, 2007)
The expediency of studying the relative movement of magnetically levitated train with the use of mathematical modeling has been substantiated. Proceeding from results of alternative options of such modeling, advantages of its tensor techniques are shown. The order of required model construction with the use of these techniques has been tracked.